A COMPARISON OF MIDAZOLAM AND MINI DOSE SUXAMETHONIUM TO FACILITATE LARYNGEAL MASK AIRWAY INSERTION DURING PROPOFOL ANESTHESIA - ALAMGIR , AR; SHAFIQ , S; AHMED , U; FAROOQ , U; CHAUDHRY , TM; NAZEER , T (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to compare the effectiveness of two different drug combinations used for general anesthesia during laryngeal mask airway (LMA) insertion. One group received Propofol-Midazolam (PM), and the other Propofol-Suxamethonium (PS). The study assessed pre-insertion conditions like mouth opening, gagging, coughing, patient movements, and laryngospasm, as well as hemodynamic parameters such as systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP) and heart rate (HR) in both groups. It also studied patient responses after LMA insertion, including apnea, cyanosis, desaturation (SpO₂ < 90%), aspiration/regurgitation, and airway injury. The primary objectives of the study were to compare the ease and success of LMA insertion when using Propofol with Midazolam and Propofol with low-dose suxamethonium and to compare variations in hemodynamic and the occurrence of complications during and after LMA insertion. The study included 110 male and female patients aged 18-40, classified as ASA 1 & 2, and scheduled for surgery under general anesthesia. The patients were randomly assigned to the PM and PS groups, and non-probability sampling was employed. In the PM group, patients were given intravenous midazolam (0.04 mg/kg) four minutes before induction with propofol (2.5 mg/kg), while in the PS group, patients received suxamethonium (0.1 mg/kg) 30 seconds after induction with propofol (2.5 mg/kg). Nalbuphine (0.1 mg/kg) was administered to all patients as an analgesic before surgery. The adequacy of anesthesia was assessed by the loss of response to verbal commands and the absence of excitatory movements. Patients were evaluated for their response to LMA insertion attempts, including the absence of excitatory movements, mouth opening, and the number of attempts required. Patient responses to gagging, coughing, movements, laryngospasm, desaturation, and apnea duration were noted. Hemodynamic changes before induction, as well as before and after LMA insertion, were recorded. Data was entered into SPSS version 15, and the mean standard deviation was calculated for age, weight, SBP, DBP, MAP, HR, SpO₂, and apnea duration. Qualitative and quantitative data were analyzed using the chi-square test and t-test, respectively, with significance set at a p-value < 0.05. Laryngeal masks were successfully inserted into the hypopharynx in the first attempt in 100% of patients in both the PM and PS groups. Gagging and patient movements were observed in only 4 (7.27%) out of 55 patients in the PM group. Hemodynamic variations more significant than 20% from baseline (before anesthesia induction) were compared before and after LMA insertion. Significant differences between the PM and PS groups were observed in SBP, DBP, MAP, and HR (p < 0.05). The apnea duration was 2.10 ± 1.51 minutes in the PM group and 1.01 ± 0.49 minutes in the PS group, with a significant p-value of 0.044. However, there were no cases of SpO₂ falling below 90% in either group. The study concluded that midazolam and a small dose of suxamethonium during propofol anesthesia were comparable in terms of ease and success of LMA insertion. The PM group exhibited better hemodynamic stability than the PS group, except for apnea duration, which was shorter in the PS group. There was no significant difference in SpO₂ levels between the two groups.